Glucose‐6‐phosphate dehydrogenase deficiency and intracranial atherosclerotic stenosis in stroke patients. (7th June 2022) - Li, Jianle; Chen, Yicong; Ou, Zilin; Zhang, Yusheng; Liang, Zhijian; Deng, Weisheng; Chen, Hao; Huang, Weixian; He, Yingxin; Xing, Shihui; Yu, Jian; Zeng, Jinsheng
Abstract: Background and purpose: Intracranial atherosclerotic stenosis (ICAS) is a major cause of stroke in Asian countries. Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency, a hereditary enzyme defect prevalent in Asian countries, has been associated with atherosclerotic cardiovascular disease and worse poststroke outcomes. However, the impact of G6PD deficiency on ICAS remains unclear. We aimed to compare the risk of ICAS in stroke patients with and without G6PD deficiency in a Chinese cohort. Methods: We prospectively and consecutively recruited stroke patients from four centers in China. All patients received intracranial artery assessment by magnetic resonance/computed tomography angiography or digital subtraction angiography, as well as G6PD enzyme evaluation. The prevalence, burden, and characteristics of ICAS were compared between patients with and without G6PD deficiency using multivariate regression analysis. Results: Among 1593 patients, 116 (63.7%) of 182 patients with G6PD deficiency and 714 (50.6%) of 1411 patients with normal G6PD levels were identified as ICAS. Age, hypertension, diabetes, and G6PD deficiency were independent predictors of ICAS. Among patients with ICAS, G6PD‐deficient individuals were more likely to have multiple (≥2 segments) intracranial stenosis (odds ratio [OR] = 1.87, 95% confidence interval [CI] = 1.25–2.81, p  = 0.002). G6PD deficiency increased the risk of ICAS in patients who were male (OR = 1.82, 95% CI = 1.24–2.66, p  = 0.002), aged ≥70 years (OR = 2.40, 95% CI = 1.33–4.31, p  = 0.004), or hypertensive (OR = 1.88, 95% CI = 1.28–2.77, p  = 0.001). Conclusions: Stroke patients with G6PD deficiency have a higher prevalence and ICAS burden than those with normal G6PD, particularly those who are male, older, and hypertensive. Abstract : This study compared the risk of intracranial atherosclerotic stenosis (ICAS) in stroke patients with and without G6PD deficiency in a Chinese cohort. We found stroke patients with G6PD deficiency have a higher prevalence and ICAS burden than those with normal G6PD, particularly those who are male, older, and hypertensive.